The Dynamics of Lazarus Batik Industry House in Kaliwates District Jember Regency 2012-2018 - Blandina Vintima Bari; Kayan Swastika; Mohamad Na'im; Akhmad Ryan Pratama (History Education, University of Jember, 2021)
The Lazarus Batik Industry House is a hereditary business and is a Madurese batik business whose motives are always changing. The problems in this research are: (1) What is the background for the establishment of the Lazarus batik industrial house ?; (2) What are the dynamics (capital, labor, production, marketing) of the Lazarus batik industrial house in 2012-2018 ?. The method used in this research is the historical method with stages; heuristics, criticism, interpretation and historiography. The results of this study include the background of the Lazarus batik production house, including: (1) Economic aspects; (2) The desire to preserve Indonesian cultural batik; (3) There is a hobby of interest and interest in batik; (4) Creating employment opportunities for the surrounding community; (5) Meet market needs. The process of Lazarus' business activities can be seen from several aspects through the initial capital used, the batik production section, raw materials and marketing activities. Marketing in early 2012 was still very little, because there were still many mistakes in production so that the cloth was still not suitable for sale, and the public's low interest in batik. From 2013 to 2018, the development of batik sales has increased. Since 2013 Lazarus has received orders from outside the region, the Lazarus batik market has slowly begun to expand. Not only individuals, many agencies also order this Lazarus batik, the market is no longer national but has expanded overseas. Keywords: Lazarus Batik, Industry, Dynamics.